The Theoric Fund, the Athenian finance in the 330s, and Apollodorus (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2018)
This article examines the history and role of the Theoric Fund in Athens, focusing on evidence and arguments in the long-running debate about whether a legal prohibition existed against channeling the surplus budget money designated for the Theoric Fund to military purposes. The argument here is that Libanius’ reference to this prohibition as being enforced by the death penalty for at least some time in the 340s cannot simply be rejected by adducing the evidence about either the proposal to have a public vote on diverting this money for military purposes, as was moved by Apollodorus in the early 340s, or the way in which the Theoric Fund operated in the 330s and 320s